The Effect of Service Quality and Educational Infrastructure on Student Satisfaction At MTs An-Nizhomiyah Depok - Septi, Ade; Hidayat, Aris (Management Research Studies Journal, 2024)
This study discusses the Influence of Service Quality and Educational Infrastructure on Student Satisfaction at MTs An-Nizhomiyah. By using a quantitative method with data obtained by giving a questionnaire to 74 students as respondents. This study aims to find out simultaneously whether the quality of services and the education market affect student satisfaction. The hypothesis carried out is that it is suspected that there is an influence of the quality of service and educational infrastructure on the satisfaction of MTs An-Nizhomiyah students. By using the SPSS analysis test tool, the value in the Model Summary table with an R value of 0.746 was obtained, which means that it shows a strong relationship between service quality and educational infrastructure on student satisfaction. R square is a coefficient of determination that shows the percentage of influence of service quality and educational infrastructure on student satisfaction. The R square value of 0.557 shows that the influence of the quality of educational services and infrastructure together (simultaneously) on student satisfaction. The regression equation formed Y = 6.332 + 0.700 X1 + 0.133 X2 is a positive sign meaning that if the quality of service (X1) and Educational Infrastructure (X2) are improved, it can increase student satisfaction at MTs An-Nizhomiyah (Y).